Characteristics of Patients with Non-Malignant Pleural Effusion in dr. Zainoel Abidin Hospital Banda Aceh in 2019 - Putra, Teuku Romi Imansyah; Maya, Price; Hasan, Maryatun; Pranata, Agung; Salsabila, Safira; Sariningrum, Hesti Ariandani (UI Scholars Hub, 2022)
Introduction. Pleural effusion occurs when there is a pathological process causing fluid to accumulate in the pleural cavity. Pleural effusion is still the main cause of respiratory distress and can also be caused by many diseases either from pleural, lungs, or even extrapulmonary problems. The morbidity and mortality of this condition are directly associated with the underlying causes. The aim of this study is to investigate the profile of the patients, etiology, location, fluid characteristics, comorbidities, and also the bacteria pattern of non-malignant pleural effusion. Methods. This is a retrospective descriptive study thatused patient’s medical records from January to December 2019 in Zainoel Abidin Hospital, Banda Aceh as the source of data for this study. Results. There were 118 patients with non-malignant pleural effusion from January to December 2019. In this study, it was found that the highest gender was male (66.9 %) and in the age group of 46-55 and >65 years old in male, and 56-66 years old in female. The most frequent etiology of non-malignant pleural effusion was pneumonia. The majority (72.9%) of pleural effusion were exudate and mostly happened in the right lung (53.4%). Comorbidities were found in 104 patients and the main comorbiditywas tuberculosis (11.3%). The result of the pleural fluid culture test showed that there were 33 samples with positive results. Staphylococcus hominis was the bacteria found in most of the isolates (22.9%).Conclusion. Non-malignant pleural effusions are generally exudates with Staphylococcus hominis being the most common bacterial growth